Intergenerational transmission of entrepreneurship: An East African perspective of SME owner’s choice of joining the family business or independent own founding - Sarah W Muigai; Edward Mungai; Ramakrishna Velamuri (Cogent Business & Management)
Drawing from the lens of entrepreneurship as a contextually driven phenomenon, this study examined the effects of parental business exposure (PBE) on the entrepreneurial mode of entry (EME) of the next-generation family members and the role of exposure to self-employed grandparents and motivation to venture on the relationship between PBE and EME. A survey administered to a sample of 440 SME owners in Kenya who had one or both entrepreneurial parents indicated that PBE significantly and positively influences joining the family business and significantly and negatively impacts the independent own founding EME. Both exposures to self-employed grandparents and necessity entrepreneurship motivation improve the positive relationship between PBE and joining the family business EME. By investigating the role of these two factors in the intergenerational transmission of entrepreneurial behaviour that are of keen interest in a developing country context like Kenya, this study provides practical guidance to family businesses in these contexts on the importance of extended households and a post-entry phase training of the next-generation family business entrepreneurs in shaping the next-generation leaders of family businesses.